3D numerical investigation of mechanized twin tunnels in soft ground – Influence of lagging distance between two tunnel faces. (15th February 2016) - Do, Ngoc-Anh; Dias, Daniel; Oreste, Pierpaolo
Highlights: A strong effect of the lagging distance between mechanized tunnel faces on twin tunnels excavation has been highlighted. The tendency in the change of the bending moment and lining deformation in tunnels depending on the lagging distance are generally opposite. The critical lagging distance between two tunnel faces in terms of the lining stability is equal to 1 LS . Abstract: During the construction of twin mechanized tunnels, a large impact of lagging distance is expected due to the strong effects of external loads and also the time dependence of the tunnel behaviour along the direction of tunnelling. Most researches in the literature focused on the influence of the distance between the tunnels' axis and their relative position. In this study, a 3D numerical investigation was carried out of the interaction between twin mechanized tunnels excavated in a horizontally parallel section. Special attention was paid to the influence of the lagging distance between the two mechanized tunnel faces. The numerical results indicated that the critical situation in terms of the lining stability occurs when the face of the following tunnel is at the same transverse section as the preceding tunnel. The tendency in the change of the bending moment and the lining deformation in the preceding tunnel and the following tunnel are generally opposite, depending on the lagging distance.